Non-Parametric Approach to Measuring Accuracy Of Social Assistance Programs in The Middle of Indonesian Economic Downturn - Darman Saputra; Julia Julia (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2021)
This study aims to analyze the relationship and influence of social assistance on the number of poor people in Indonesia. There are control variables as a comparison, namely; unemployment, central government debt and economic growth. The research method used a quantitative approach with non-parametric statistics, annual data (2013-2020) and elasticity were used to measure the magnitude of changes in the number of poor people due to additional social assistance. Rank Spearman test to test the relationship of each variable (total unemployment, central government debt and economic growth) to the amount of poverty in Indonesia. The results showed that there was a very strong relationship between social assistance for Contribution Assistance Recipients (PBI) and the Family Hope Program (PKH) on the number of poor people. The negative sign indicates that social assistance can reduce poverty significantly, with the strongest impact being the PBI program. There is a strong relationship between debt and the number of poor people. The slowdown in economic growth is proven to be unrelated to the number of poor people, meaning that in the midst of an economic slowdown, the amount of poverty in Indonesia can be suppressed through social assistance programs, job creation as laborers and government debt is allocated for productive activities and economic activities that have a direct impact on the poor and vulnerable to poverty. Poverty alleviation efforts can be carried out by the government by synergizing social assistance programs and creating job opportunities according to the ability of the poor on average.